Pembangunan Sistem Helpdesk Ticketing Berbasis Web Menggunakan Framework Laravel - Ahmad Muhajir; Eko Darmanto (Politeknik Piksi Ganesha Indonesia, 2026)
The Information Systems Institute (LSI) of Muria Kudus University (UMK) plays a crucial role in providing technical support (IT Support) for all work units and academics. In daily operations, communication processes and constraints have been responsively managed through telephone lines and instant messaging platforms (such as WhatsApp and SMS). However, the high volume of requests poses administrative challenges, with reports often leading to bottlenecks in certain individuals, prone to being lost, and the lack of an integrated ticketing system making it difficult for strategic units such as LSI, BAAK, and BAU to concisely compile recapitulation data. To improve this communication flow,